Virtual reality for sensorimotor rehabilitation post stroke: design principles and evidence - Bermúdez i Badia, Sergi (2019)
n the recent years, the use of virtual reality (VR) to enhance motor skills of persons with activity and participation restriction due to disease or injury has been become an important area of research. In this chapter, we describe the design of such VR systems and their underlying principles, such as experience-dependent neuroplasticity and motor learning. Further, psychological constructs related to motivation including salience, goal setting, and rewards are commonly utilized in VR to optimize motivation during rehabilitation activities. Hence, virtually simulated activities are considered to be ideal for (1) the delivery of speciﬁ c feedback, (2) the a bility to perform large volumes of training, and (3) the presentation of precisely calibrated difﬁ culty levels, which maintain a high level of challenge throughout long training sessions. These underlying principles are contrasted with a growing body of research comparing the efﬁ cacy of VR with traditionally presented rehabilitation activities in persons with stroke that demonstrate comparable or better outcomes for VR. In addition, a small body of literature has utilized direct assays of neuroplasticity to evaluate the effects of virtual rehabilitation interventions in persons with stroke. Promising developments and ﬁ ndings also arise from the use of off-the-s helf video game systems for virtual rehabilitation purposes and the integration of VR with robots and brain-computer interfaces. Several challenges limiting the translation of virtual rehabilitation into routine rehabilitation practice need to be addressed but the ﬁ eld continues to hold promise to answer key issues faced by modern healthcare.